2004
DOI: 10.1016/s0377-1237(04)80103-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Drug Susceptibility pattern of Mycobacterium tuberculosis in HIV infected Patien

Abstract: Incidence of HIV infection in patients with tuberculosis was found out by serological method (ELISA) with confirmation by Western Blot analysis. Out of 2116 tuberculosis patients tested for HIV, 150 cases were found to be positive for HIV infection (5.73%). Drug susceptibility to first line antitubercular drugs was carried out in 1378 isolates from HIV negative cases and 68 isolates from AIDS cases. The overall resistance pattern to one or more drugs was seen in 13.78% of isolates from HIV negative cases as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
2
6
1
Order By: Relevance
“…Out of the 443 clinical samples collected, 76 samples yielded growth of Mycobacteria. Our HIV-TB co-infection rate of 41% concurs with the studies of Zambia -43%, [23] Pune -45.3%, [24] Vadodara,Gujarat-49.2%, [25] South African-49%, [26] Southern California -43.2% [27] and Benin, Nigeria -33.9%. [28] Wide disparity was observed in a Tanzanian study which showed low co-infection rate of 5.3%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Out of the 443 clinical samples collected, 76 samples yielded growth of Mycobacteria. Our HIV-TB co-infection rate of 41% concurs with the studies of Zambia -43%, [23] Pune -45.3%, [24] Vadodara,Gujarat-49.2%, [25] South African-49%, [26] Southern California -43.2% [27] and Benin, Nigeria -33.9%. [28] Wide disparity was observed in a Tanzanian study which showed low co-infection rate of 5.3%.…”
Section: Discussionsupporting
confidence: 89%
“…The other two species identified in their study were M. Kansasiand M. bovis. [31] Our study differs from studies of Praharaj et al of Pune [24] who reports only MTB with no atypical Mycobacteria and study of Murcia-Aranguren et al of Bogota, in which M.avium was the predominant species 13(4.2%) and MTB was only 4(1.4%). [32] In this study blood culture was found to be positive in 18 (11%) out of 162 samples and 13 patients were found to have TB only by blood culture.…”
Section: Discussioncontrasting
confidence: 81%
“…From the same centre, higher incidence of drug resistance in 17.14% cases was reported in another study carried in 1995-98 [19]. Over all drug resistance of 13.8% in non HIV patients has recently been reported from another armed forces hospital [20].…”
Section: Discussionmentioning
confidence: 63%
“…There have been reports of drug resistant tuberculosis from various parts of India [9][10][11][12][13][14][15] and the world [16,17] but only a few reports from the armed forces [18][19][20]. It is interesting that almost similar figure of drug resistance (12.70%) to MTB was reported in a study conducted in 1992-93 among soldiers and their families from a tertiary chest disease centre [18].…”
Section: Discussionmentioning
confidence: 87%
“…The prevalence of pulmonary tuberculosis among the HIV positive persons, in the present study is 53 (88.33%). The prevalence of co-infection with HIV varies widely across regions [9][10][11][12][13][14] within India and outside India mainly due to the variation in the distribution of risk factors, geographic location, awareness levels etc. of the study population.…”
Section: Discussionmentioning
confidence: 99%